Counterfeit Goods and Income Inequality - Scandizzo, Stefania (Washington, D.C. : International Monetary Fund, 2001)
This paper examines the effect of counterfeit goods in a world where consumers are differentiated by level of income and innovation is quality enhancing. Counterfeit goods are defined as products with the same characteristics as 'originals', but of lower quality. The effect of imitation on firms' profits and consumer welfare depends on the distribution of income within the country. In particular, the greater the level of income inequality the larger the increase in consumer welfare due to the imitation, and the smaller the effect on profits of the state-of-the-art firm.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet